Distribution, morphology, phytochemical composition, and antioxidant activity of Mediasia macrophylla (Apiaceae) from the Western Tien Shan, Kazakhstan - FURKAT A. UBAEV; ANAR M. ESIMOVA; ZHANAR E. AIMENOVA; ZHANAR B. ISKAKOVA; AINAGUL KOLPEK; ZHANAR B. TEKEBAYEVA; AIDANA BAZARKHANKYZY; NURGUL ASKAROVA (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Ubaev FA, Esimova AM, Aimenova ZE, Iskakova ZB, Kolpek A, Tekebayeva ZB, Bazarkhankyzy A, Askarova N. 2026. Distribution, morphology, phytochemical composition, and antioxidant activity of Mediasia macrophylla (Apiaceae) from the Western Tien Shan, Kazakhstan. Biodiversitas 27 (3): d270315. https://doi.org/10.13057/biodiv/d270315. Mediasia macrophylla (Apiaceae) is a perennial Central Asian species with reported medicinal relevance; however, integrated ecological, morphological, and phytochemical data for populations in Kazakhstan remain limited. The present study provides a preliminary, exploratory, site-based characterization of M. macrophylla from two natural populations within the Aksu-Zhabagly State Nature Reserve (Western Tien Shan, southern Kazakhstan). Habitat conditions, quantitative morphology, essential oil composition, and antioxidant activity of solvent extracts were assessed. Field surveys confirmed that the species occurs in restricted, localized populations associated with rocky limestone slopes and meadow-steppe habitats. Quantitative morphometric analysis of mature, flowering individuals (n = 20) showed moderate variation in vegetative traits and comparatively conservative reproductive and fruit morphology, consistent with stable diagnostic morphology at the local population level. Essential oil composition was determined by GC-MS using a single pooled sample, revealing 29 compounds accounting for 95.83% of the total oil. Antioxidant activity of pooled solvent extracts was evaluated using FRAP and DPPH assays with technical replication. Phytochemical and antioxidant data were obtained from pooled material and technical replicates only and are therefore interpreted descriptively. A clear solvent-dependent pattern was observed: the ethyl acetate extract showed the highest Ferric Reducing Capacity (FRAP absorbance 1.17 at 1.0 mg/mL), whereas the ethanol extract exhibited the strongest radical scavenging activity (80.62% DPPH inhibition at 1.0 mg/mL), approaching that of gallic acid (86.14%). The chloroform extract displayed consistently weak activity. Overall, the results provide descriptive, hypothesis-generating data on the ecological context, morphology, and phytochemical and antioxidant profiles of M. macrophylla within the Aksu-Zhabagly Reserve and highlight the need for replicated, multi-site, and multi-season studies to assess population-level variability and potential chemotypic patterns.